in brief - Grigoryeva, Elena (project baikal, 2021)
This news section presents the awards received by Irkutsk architects, the meetings  of the RAACS and the Union of Architects of Russia, as well as other architectural events.
Keywords: awards; RAACS; Union of Architects of Russia